Prevalence and types of cardiovascular disease in Cocker Spaniels presented to University Veterinary Hospital, Universiti Putra Malaysia (2012–2014) - Goh, C. Y.; Khor, K. H.; Dhaliwal, Gurmeet Kaur; Megat Abdul Rani, Puteri Azaziah; Lau, S. F.; Watanabe, Malaika (2015)
Acquired valvular disease is the most commonly encountered cardiovascular disease in veterinary practice, followed by myocardial diseases. Cocker Spaniels are known to be predisposed to chronic degenerative valvular disease (CDVD) and dilated cardiomyopathy (DCM). A retrospective study was conducted to evaluate the prevalence and types of cardiovascular disease in Cocker Spaniels presented to University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) from 2012–2014. A total of 98 Cocker Spaniels were presented to the hospital, and 20 dogs had confirmed cardiac disease, while 5 cases had potential cardiac disease. Among the confirmed cases, the most common diagnosis was acquired valvular disease (52%), followed by myocardial disease (12.72%) by a large margin. One dog was diagnosed with DCM and concomitant CDVD; while only one dog was diagnosed with DCM. Another dog was diagnosed with a heart-base tumour. The average age at diagnosis was 9.4 years (range: 3–15 years old), while the youngest age at diagnosis was 3 years old. Interestingly, 55% of the confirmed cases were female, while only 45% were males. Dogs having cardiac disease may be asymptomatic; therefore the prevalence rate could be under-represented. Thus, an early screening for cardiac disease at young age is recommended.